Four new neotropical species and a new combination of Urera (Urticaceae) - Steinmann, Victor W. (Instituto de Ecología, A.C., 2005)
The pantropical genus Urera (Urticaceae) has been taxonomically neglected in present times. Approximately ten species of the genus occur in Mexico with an additional four in Central America. In this article, taxonomically useful characters for the Mexican and Central American taxa are provided and some of the taxonomic problems associated with these species are discussed. Four new species are proposed (Urera glabriuscula, U. martiniana, U. pacifica, and U. rzedowskii), and a new combination (Urera verrucosa) is made.